Fenomena Thrifting di Pasar Loak Jembatan Item Jatinegara - Pascal Adinata Susanto; Abdul Haris Fatgehipon; Sujarwo (PT. PENERBIT TIGA MUTIARA, 2024)
The phenomenon of thrifting at Pasar Loak Jembatan Item Jatinegara demonstrates the continuity and evolution of frugal shopping practices involving the purchase of second-hand items. This research delineates the long history of thrifting, from the medieval period to the emergence of organizations such as Salvation Army and Goodwill that popularized it in the 19th century. The COVID-19 pandemic has reignited interest in thrifting due to economic pressures prompting people to save on expenses. The research methodology employed is qualitative descriptive, utilizing in-depth interviews and direct observations at Pasar Loak Jembatan Item Jatinegara. The findings reveal that traders employ two main strategies: selling directly at the market and through online platforms. Meanwhile, consumers have diverse motivations, ranging from meeting household needs to a desire to collect unique and antique items. Analysis of Alfred Schutz’s phenomenological theory is used to understand the reasons and goals behind consumer’s choices in thrifting. The researcher finds that each individual has different motives, such as goal motives (In order to motive) and because motives (Because motive), underlying their decisions to engage in thrifting. The conclusion of this research is that the phenomenon of thrifting at Pasar Loak Jembatan Item Jatinegara reflects the evolving and relevant dynamics of consumer culture, adapting to social and economic changes. With the evolution of this practice, the second-hand market becomes a favorite place for people to find affordable items, while traders and consumers continue to adapt to technological advancements and changes in the economic landscape. This study provides valuable insights into how thrifting is not just an economic phenomenon but also reflects the identity and preferences of consumers in a constantly changing shopping culture.